2020
DOI: 10.21913/jdrssesw.v1i1.1042
|View full text |Cite
|
Sign up to set email alerts
|

Napping on night shift: Powerful tool or hazard?

Abstract: N/A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Ruggiero and Redeker [ 17 ] found that many individual characteristics such as age, gender, and years of experience can influence the potential positive effects of napping. Naps of 20-40 minutes have been reported to have the most beneficial effects, while the effects of short naps lasting to a maximum of 10 minutes are largely unknown [ 18 ]. Despite these potential positive effects, many workers do not apply napping as a recovery activity since they presume that naps take too much time and they fear feeling worse afterwards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruggiero and Redeker [ 17 ] found that many individual characteristics such as age, gender, and years of experience can influence the potential positive effects of napping. Naps of 20-40 minutes have been reported to have the most beneficial effects, while the effects of short naps lasting to a maximum of 10 minutes are largely unknown [ 18 ]. Despite these potential positive effects, many workers do not apply napping as a recovery activity since they presume that naps take too much time and they fear feeling worse afterwards.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these potential positive effects, many workers do not apply napping as a recovery activity since they presume that naps take too much time and they fear feeling worse afterwards. Moreover, they feel they are too busy or do not have a comfortable napping space and they feel that the management would not support them in taking a nap during work [ 18 ]. We are not aware of articles that describe intervention studies focusing on other types of relaxations or work stress reduction techniques for shift workers.…”
Section: Introductionmentioning
confidence: 99%